Evaluation of an intuitive 4WD drift assist control concept in a driving simulator - Sun, Yiwen; Velenis, Efstathios; Krishnakumar, Ajinkya (Taylor & Francis, 2025)
In this paper, we present a concept of drift assist control for a 4-Wheel-Drive (4WD) electric vehicle that allows independent wheel torque control, aiming at an intuitive interaction with the average human driver. The concept is evaluated through a driver-in-loop trial using a driving simulator. Starting with a 4WD drift equilibrium analysis, we demonstrate the necessity of incorporating the throttle input for sideslip control and the idea of restricting the sideslip rate in order to assist the driver in stabilising the vehicle in drifting. Subsequently, we design a sideslip rate and yaw rate controller according to the desired sideslip angle from the driver using torque vectoring. To evaluate our control concept, a circular track is built in Cranfield University’s driving simulator based on the IPG CarMaker software. 34 participants were recruited to perform two drifting tasks, including the transition from normal cornering to drifting and regulating the sideslip under different configurations of sideslip damping rate and steering wheel feedback torque. Through subjective questionnaires and objective evaluation of vehicle states, the results show that our concept can assist the driver in intuitively controlling the vehicle during drifting.
Keywords: 4007 Control Engineering, Mechatronics and Robotics; 40 Engineering; 4010 Engineering Practice and Education; 7 Affordable and Clean Energy; Automobile Design & Engineering; 40 Engineering; 49 Mathematical sciences; Drift assist control; torque vectoring; driver-in-loop trial; vehicle dynamics